The Critical Role of Health Practitioners in Saving Accident Victims: A Comprehensive Review - AL Anazi, Hala Ahmad; AL Mutairi, Meshari Mohammed; AL Mutairi, Saad Saeed; AL Mutairi, Faris Barky; AL Shammari, Maram Hlayel; AL Dohyan, Meshal Meshari; AL Ruwaili, Sayer Ofyer (International Journal of Medical Toxicology and Legal Medicine, 2024)
Accidents represent one of the leading causes of morbidity and mortality worldwide, making the role of health practitioners in saving victims a matter of global importance. This review synthesizes current evidence on the contribution of health practitioners in accident response, spanning pre-hospital interventions, emergency trauma care, surgical management, rehabilitation, and psychological support. Emphasis is placed on the time-sensitive nature of interventions, multidisciplinary collaboration, and advances in training and technology. The findings reveal that early intervention by trained practitioners significantly improves survival rates, reduces disability, and enhances recovery outcomes. The article concludes with recommendations for strengthening training, infrastructure, and policy frameworks to empower health practitioners in accident care.